Book reviews: Daniel Kahneman - Thinking, Fast and Slow - Uta, Cristian (Annals of Spiru Haret University. Economic Series, 2016)
Although he has won the Nobel Prize for Economy (for his works on the decision theory), Daniel Kahneman is, surprisingly, a psychologist. Thinking, Fast and Slow presents us ideas and theories regarding the way in which the mind works and how this thing affects us when making a decision. In his opinion, the human thinking is a dual process, duality presented from three different perspec-tives. First (as the title suggests it), there are highlighted the differences between the fast and the slow thinking. Then the distinction between econs (rational agents of the classical economic theory and of the importance of economic schools of Chicago) and humans (real people, which are not irrational but to whom the rational model does not fit) is argued. Finally, the author presents us the conflicts between the remembering self and the experiencing self in respect to the way in which these selves perceive the wellbeing. The volume contains 38 chapters structured in five parts. At the end, there is a Conclusions section and there are attached two articles written by Kahneman together with his friend Amos Tversky which present the contributions that have been cited by the Nobel committee for justifying the award given in 2002 (Tversky died in 1996 and he could not be awarded the Nobel Prize, although he would have deserved it).